Monitoring wellness, training load, and running performance during a major international female field hockey tournament - McGuinness, A.; McMahon, G.; Malone, S.; Kenna, D.; Passmore, D.; Collins, K. (The Journal of Strength and Conditioning Research, 2020)
The current observational study quantified players' activity profiles during a major international female field hockey tournament and determined whether an association exists between well-being measures and running performance within elite female hockey players. Elite female field hockey players (23 ± 3 years; 162.6 ± 13 cm; and 66 ± 6 kg) participated in the study. Participants running performance was monitored using global positioning system technology (S5; Catapult Innovations, Scoresby, Victoria, Australia), with daily well-being questionnaires used to quantify player responses during the tournament. Thresholds for the magnitude of the observed change for each variable were determined using the Hopkins Spreadsheets for analysis of controlled trials. Relative distance (m/min) was likely lower when compared with game 1 in game 7. Relative high speed (m·min-1 >16 km/h) was likely lower in games 5, 6, and 7 when compared with game 1. Subjective load was very likely higher in game 2 and very likely lower in game 3 when compared with game 1. Mood and sleep quality were likely lower in game 1 when compared with game 4 and game 7. Muscle soreness was likely higher when compared with game 1 in game 7. During the tournament, it was observed that a decrease in players' daily well-being was accompanied by changes in running performance. Furthermore, changes to players' muscle soreness and sleep quality result in decreased players' high-speed running performance during match-play. Therefore, to prevent the observed effects, coaches should adopt strategies to enhance sleep quality and incorporate specific recovery modalities to reduce musculoskeletal soreness.